The effects of increased absolute training intensity on adaptations to endurance exercise training - McNicol, A. J.; O`Brien, B. J.; Paton, C. D.; Knez, W. L. (Journal of Science and Medicine in Sport, 2009)
"Progressive overload" is regarded an important principle to consider in maximising endurance training adaptations, yet little scientific evidence supports this concept. The aim of the present study was to compare differences in endurance performance after a training regime where treadmill-running intensity was incrementally elevated to a regime where running intensity remained unchanged. Twenty-eight healthy untrained males and females were randomly and equally assigned into both regimes. All participants performed 20 min treadmill-running sessions 3 times a week for 6 weeks. Prior to and after training, maximum oxygen uptake (image), oxygen uptake and velocity at the lactate threshold (LTVO2 and LTv) and maximum treadmill velocity (Vmax) were measured in an incremental treadmill test. 5000 m time trial performance was also assessed. In the incremental intensity regime treadmill velocity commenced at 0.8 km·h-1 below the LTv and was increased by 0.1 km·h-1 every session. In the constant intensity regime treadmill speed was kept constant at 0.8 km·h-1 below the LTv for the duration of the training. The study revealed that both regimens increased image, Vmax LTVO2, LTv and decreased 5000 m time trial significantly after training. There were no significant differences in the changes between regimens for image, Vmax and 5000 m time trial. However, the increase in LTVO2 and LTv were significantly greater in the incremental intensity regime compared to the constant intensity regime. The present data show that 20 min treadmill-running sessions performed 3 times a week for 6 weeks improves endurance performance and that progressively elevating exercise intensity is important to maximise improvements in LTVO2 and LTv.